Performance of sacrificial anodes in the rehabilitation of corrosion affected Finger jetty - Rajendran, V.; Murugesan, R. (Journal of Structural Engineering, 2024)
The increase in the number of structures affected by corrosion has created more awareness in the minds of the researchers to investigate the various corrosion protection methodologies to be adopted during and after the completion of construction of reinforced concrete structures. Usage of different types of surface coating on rebars for the corrosion protection has some disadvantages on account of many factors, like reduction in bond stress between the concrete and rebar and so on. The attempts of the various rehabilitation organizations in restoring the corrosion affected structural elements back to their original load carrying capacity has proved to be a very complicated process and a short lived one. Such rehabilitation methods involve exorbitantly high costs, besides causing a lot of disturbance to the occupants. Hence recourse is being made by researchers as well as repair and rehabilitation experts to identify newer and cost effective corrosion control techniques that will give long term satisfactory performance. One such method that is being widely and successfully employed all over the world is the self regulating sacrificial galvanic protection system. The paper describes in detail investigations conducted on a corrosion damaged Finger jetty, the repair methodology suggested for the rehabilitation of the structure and executed. The repair methodology proposed included the provision of galvanic anodes. The paper also describes in detail the monitoring of the repaired Finger jetty through half cell potential and ultrasonic pulse velocity measurements conducted over a period of one and a half years from the time of completion of the repair to assess the effectiveness of the repair methodology. The investigations have clearly demonstrated that galvanic anodes have proved to be an effective corrosion control technique for reinforced concrete structures.